(untitled) (Experimental biology, 2016)
Polyunsaturated fatty acids are a unique class of organic compounds that play an important role in biological systems. These acids in the process of metabolic transformations effect the cardiovascular, nervous, reproductive and immune systems of the body, and their derivatives are used for the production of various compounds, applicability in agriculture, veterinary medicine, medicine, cosmetics and food industry. In mammalian organism polyunsaturated fatty acids can not be synthesized de novo and must enter from outside. Currently, as sources for obtaining polyunsaturated fatty acids used vegetable oils and seafood. In animal fats polyunsaturated fatty acid content is negligible. Due to the decrease of fish stocks, suitable for planting lands, the actual problem is to find new sources of polyunsaturated fatty acids that are potentially suitable for biotechnological research in the field of production. Promising producers of lipids and polyunsaturated fatty acids are considered microorganisms because of their high growth rate on simple media and ability to accumulate large amounts of lipids and of individual representatives polyunsaturated fatty acids, as well as the ability to manipulate their metabolism. The aim of this study was the selection of microorganisms isolated from the soils and freshwater of Kazakhstan, containing valuable polyunsaturated fatty acids. The object of this study was the microscopic fungi, yeasts and bacteria isolated from freshwater and soil of Kazakhstan: Penicillium сitrinum, Penicillium restrictum, Penicillium bilaiae, Penicillium aculeatum, Petromyces alliaceu, Aspergillus sp., Mucor circinelloides, and Rhodotorula mucilaginose, Auerobasidium commune, Yarrowia lipolytica, Kocuria erythromyx, Bacillus еndophyticus, Rhodococcus roseae. In this study we use methods of cultivation of microorganisms, lipid extraction by the method Cates and Garbus, gravimetric method, gas chromatography. In work was studied the lipid content and fatty acid composition of filamentous fungi, yeasts and bacteria isolated from freshwater and soil of Kazakhstan. It was shown that the investigated microorganisms contain lipids from 4,3±0,4% to 15,1±1,5% from the dry weight and contain practically important polyunsaturated fatty acids as linoleic, α - and γ-linolenic and eicosapentaenoic. Promising as producers of valuable lipids and polyunsaturated fatty acids were selected filamentous fungi Petromyces alliaceus, Mucor circinelloides and yeast Auerobasidium commune, Yarrowia lipolytica. They can be recommended to develop the technology of obtaining practically important preparations of polyunsaturated fatty acids.